2015
DOI: 10.1039/c5ra13855h
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering of a new recombinant peptide to increase the surface contact angle of stainless steel

Abstract: Biofouling seriously affects the properties and service life of metal materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…This method was simple, enabling any peptide with available basic residues to attach to metal surfaces. Such simplicity confers significant advantage over other methods of preparing peptide-modified metal surfaces, which require extensive design, protracted chemical synthesis, or expression of specific metal-binding peptide/protein sequences [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was simple, enabling any peptide with available basic residues to attach to metal surfaces. Such simplicity confers significant advantage over other methods of preparing peptide-modified metal surfaces, which require extensive design, protracted chemical synthesis, or expression of specific metal-binding peptide/protein sequences [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, peptide-modified steel surfaces have been prepared by sharing electrons between metal and peptide disulfide bonds, resulting in reduced bacterial surface colonization by Pseudomonas aeruginosa and Staphylococcus aureus [ 9 ]. Our group has previously expressed recombinant fusion proteins containing a stainless steel-binding domain, which were used to further functionalize metal surfaces [ 10 ]. Furthermore, we examined the influence of the bioorganic modifier on surface topography for a synthetic peptide-modified 304 stainless steel [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al yielded a new bioorganic metal by the reaction of 12 amino acid peptide and stainless steel and the surface properties of the new material altered compared with the original metal . An antibacterial peptide obtained from gene‐engineered has been used to react with 304 stainless steel for generating antibacterial materials . An antimicrobial peptide, magainin II (MAG II), was discovered and isolated from the granular gland of the skin of the African frog, Xenopus laevis .…”
Section: Introductionmentioning
confidence: 99%
“…22 An antibacterial peptide obtained from geneengineered has been used to react with 304 stainless steel for generating antibacterial materials. 23 An antimicrobial peptide, magainin II (MAG II), was discovered and isolated from the granular gland of the skin of the African frog, Xenopus laevis. 24 MAG II has a broad spectrum of antimicrobial activity against Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments indicated that peptides with disulphide bond were easy to react with stainless steel. Ren et al designed and produced a peptide from Bacillus subtilis which could prepare a new material with good hydrophobicity by reacting with stainless steel . Some short‐chain peptides obtained by biological chemical synthesis were also applied to the synthesis of new materials …”
Section: Introductionmentioning
confidence: 99%